The social construction of violence among Northern Plains tribal members with antisocial personality disorder and alcohol use disorder. (February 2014) - Jervis, Lori L.; Spicer, Paul; Belcourt, Annie; Sarche, Michelle; Novins, Douglas K.; Fickenscher, Alexandra; Beals, Janette; Team, AI-SUPERPFP
Whereas recent reports from national studies have presented extremely high rates for many personality disorders in American Indian communities, persistent concerns about the meaning of these symptoms have left many troubled by these reports. American Indians as a group are known to suffer disproportionately from a number of violent experiences, but the dynamics of this violence have received little attention. This paper examines perspectives on violence in the lives of 15 northern plains tribal members who met criteria for antisocial personality disorder and comorbid alcohol use disorder. It explores how study participants constructed and understood their own violent encounters, as well as the motivations they described (characterized here as reputation, leveling, retaliation, catharsis, and self-defense). Violence was gendered in this study, with men generally presenting as perpetrators and women as victims. Men often described themselves as ready participants in a violent world, while women were quite clear that aggression for them was often simply required as they tried to defend themselves from male violence. While this analysis does not replace clinical analyses of violence in antisocial personality disorder, it does reveal an underlying cultural logic that may play a role in shaping the recourse to violence for that minority of individuals for whom it appears to be the obvious choice.